The warp of power. Electoral politics from cabildo of San Salvador de Jujuy during the XVIIth. century - Ferreiro, Juan Pablo (AWARI, 2020)
This article shows a discrete set of electoral acts drawn up between the foundation of the city of San Salvador de Jujuy in 1593 and the 1650s, as a window to political life and the construction of capitular power in early colonial Jujuy, from a microanalytical and structural perspective. For this we will identify the nuclei in which the electoral capacity will eventually be concentrated; the possible groups that participate in this political life and the historical figures that stand out in it, as well as the socio-economic relationships that developed over no less than three generations. Our research strategy consists of the use of some tools and notions provided by the Analysis of Social Networks, which allow us to collect, order, contrast, fragment, subgroup, and analyze the information obtained from the above sources.